PRODUKSI SERASAH BERDASARKAN ZONASI DI KAWASAN MANGROVE BANDAR BAKAU, DUMAI-RIAU - Ruth Herlina Sitompul; Khairijon '; Siti Fatonah (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Mangrove is flora that grows in coastal area and it has high tolerance on salinity. Mangrove plays an important role in nutrient cycle because it produces nutrient for surrounding ecosystem. Riau province has wide mangrove forest located in Dumai city, Bandar Bakau. The aim of the research was to determine the amount of its litter production. There were three zones in this research, namely Upper Zone, Middle Zone and Lower Zone. A total of 10 litter traps (1x1 m2) were placed in each zone using a purposive sampling method. The litter was analyzed in the Laboratory Ecology of Biology Department. Results showed that highest total litter production for threemonths (1091.02 g/m2/month) was found in the Middle Zone. In March, litter production (619.62 g/m2/month) was higher than the others. The data showed that the litter production had a positive correlation with humidity and rainfall in the three zones. A significant value was found in the Lower Zone between litter production and salinity.